Disability and community - Carey, Allison C.; Scotch, Richard K., 1951- (Research in social science and disability ;, 2011)
This volume of Research in Social Science and Disability brings together interdisciplinary scholarship to examine a wide array of issues related to disability and community, a topic of critical importance academically and politically. The evolving and politically contested notions of community sit at the centre of much of the recent research on disability and, as researchers both create and reflect various ideas of membership when defining 'disability' and aggregating individuals, their methodological decisions have significant implications for how we come to understand disability and community. This volume examines a wide range of social institutions and practices such as education, employment, and cultural venues and the extent to which and how they include people with disabilities in the workings of these institutions. It includes research framed by a variety of theoretical perspectives and research methodologies and offers innovative ways to envision inclusive communities and, therefore, enables us to consider how to move forward to create them.